Undergraduate students’ perceptions of teachers’ written feedback in academic writing class: A survey study - Nisa Cahyani; Banatul Murtafi'ah (Communications in Humanities and Social Sciences, 2022)
This survey study aims to describe the students’ perception of teachers’ written feedback in an academic writing class in a private university in Indonesia. 119 students filled in the questionnaire on students’ perceptions of teachers’ written feedback adapted from Ouahidi and Lamkhanter (2020). A descriptive statistic measuring mean, frequency, and standard deviation were used to analyze the data from the questionnaire. The results showed that the teacher’s written feedback to the writing results in the academic writing class was useful and students did not find it difficult to understand any feedback given by the teacher. Most of the students answered often when being asked about their understanding to the feedback. Students were also able to use teacher comments to revise their writing. Revision and rewriting were also found as the follow-up activities that are most often done by students after receiving feedback. Then, it was also revealed that students preferred their teacher to give them correction with comments to all the major errors in their writing. In addition to the feedback, students also preferred their teachers to give praise and criticism. Regarding the correction of students' writing work, students preferred the teacher to correct the errors in content or ideas. Further implications and suggestions are also discussed in this article.